A graft copolymer composition and ABS resin and preparation method and application thereof
By introducing specific monomers and surfactants into the graft copolymer, the processing stability and sporadicity problems of the preparation of ABS resin by emulsion polymerization are solved, and ABS resin with high gloss and low emanation performance is achieved.
Patent Information
- Application Number
- CN202410301069.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-15
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-03-15
AI Technical Summary
The ABS resin prepared by emulsion polymerization has problems such as poor processing stability, unstable gloss, low surface energy and high sporadic substances, which affects its performance in different applications.
By introducing maleic anhydride and alkyl acrylate monomers into the graft copolymer, the reaction conversion rate is improved and the residual monomer content is reduced; at the same time, alkynol surfactants are added to reduce additive residues and improve the processing performance and surface characteristics of the ABS resin.
The excellent processing stability, high gloss, high surface energy and low emanation performance of ABS resin is achieved, thereby improving its performance in different applications.
Smart Images

Figure QLYQS_1 
Figure QLYQS_2 
Figure GDA0005269337790000041
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polymer synthesis, and specifically relates to a graft copolymer composition and ABS resin, and a preparation method and application thereof. Background Art
[0002] ABS resin is the most widely used thermoplastic polymer material in the world, where A stands for acrylonitrile, B stands for butadiene, and S stands for styrene. ABS resin has good comprehensive properties, such as good strength, excellent impact resistance, high dimensional stability in a wide temperature range, etc., and is widely used in the fields of automobiles, home appliances, etc. The preparation methods of ABS resin mainly include emulsion polymerization and bulk polymerization. The ABS resin rubber prepared by emulsion polymerization has various designs and is more suitable for applications in multiple occasions.
[0003] However, the shortcomings of ABS resin produced by emulsion polymerization are also quite obvious. First, emulsifiers are added during the polymerization process, and these emulsifiers will remain in the system. With the subsequent high temperature and high shear processing environment, the emulsifiers are easy to degrade or precipitate, resulting in a decrease in the surface energy and gloss of the ABS resin, affecting its application in spraying, electroplating and high-gloss applications. Secondly, a large amount of unreacted monomers will remain in the latex during the emulsion polymerization process, which will make the ABS resin have a higher content of volatile substances and a stronger odor, affecting its application in places where it is in close contact with people for a long time, such as automotive interiors and kitchens. In addition, easily degradable substances and residual small molecules will make the ABS resin prone to defects such as material flowers during injection molding.
[0004] In the prior art, the above problems are mostly solved by mixing and modifying ABS resin and other chemical substances, which has the disadvantages of increasing costs, not significantly improving the effect, and failing to comprehensively improve multiple types of defects. Therefore, the present invention provides a graft copolymer composition and ABS resin to solve the above problems from the production technology, thereby increasing the types of ABS resin. Summary of the invention
[0005] The object of the present invention is to overcome the shortcomings or defects of the above-mentioned prior art of preparing ABS resin by emulsion polymerization, such as poor processing stability, unstable gloss, low surface energy, high emitting substances, etc., and to provide a graft copolymer composition and ABS resin.
[0006] Another object of the present invention is to provide a method for preparing the graft copolymer composition.
[0007] Another object of the present invention is to provide a method for preparing the ABS resin.
[0008] Another object of the present invention is to provide application of the ABS resin.
[0009] To achieve the above object, the present invention is implemented by the following technical solutions:
[0010] A graft copolymer composition, comprising:
[0011] A: 95 to 99.9 wt% of at least one graft copolymer A comprising:
[0012] Based on the graft copolymer A, 50 to 79.9 wt % of at least one graft base A1 obtained by emulsion polymerization of the following components:
[0013] A11: 60 to 99.7 wt% of butadiene monomer based on the graft base A1;
[0014] A12: 0 to 39.7 wt % of at least one aromatic vinyl monomer, based on the graft base A1;
[0015] A13: 0.1 to 1 wt % of maleic anhydride, based on the graft base A1;
[0016] A14: based on the graft base A1, 0.1 to 1 wt % of an alkyl acrylate monomer, wherein the alkyl acrylate monomer is at least one of a C1-C8 alkyl methacrylate or a C1-C8 alkyl acrylate;
[0017] A15: 0.1 to 1 wt% of an acetylenic alcohol surfactant based on the graft base A1;
[0018] wherein the sum of the weight percentages of A11, A12, A13, A14 and A15 is 100%; and
[0019] 20 to 49.9 wt. %, based on the graft copolymer A, of at least one graft shell A2, obtained by emulsion polymerization in the presence of at least one graft base A1:
[0020] A21: 40 to 99.7 wt % of at least one vinyl aromatic monomer, based on graft shell A2;
[0021] A22: 0 to 50 wt% of acrylonitrile monomer based on graft shell A2;
[0022] A23: 0.1 to 5 wt % of maleic anhydride, based on graft shell A2;
[0023] A24: based on the graft shell A2, 0.1 to 5 wt% of an alkyl acrylate monomer, wherein the alkyl acrylate monomer is at least one of a C1-C8 alkyl methacrylate or a C1-C8 alkyl acrylate;
[0024] A25: 0.1 to 1 wt% of an acetylenic alcohol surfactant based on the graft shell A2;
[0025] Wherein, the sum of the weight percentages of A21, A22, A23, A24 and A25 is 100%;
[0026] The sum of the weight percentages of A1 and A2 is 100%, and
[0027] C1: 0.1 to 5 wt% of at least one other component C1.
[0028] In the graft copolymer composition prepared in the present invention, maleic anhydride and alkyl acrylate monomers are first introduced into the graft base A1, which can improve the reaction conversion rate and greatly reduce the residual butadiene content during the polymerization process. In addition, the addition of acetylene alcohol surfactants can react on the graft copolymer, which can effectively reduce the residual amount of auxiliary agents (such as emulsifiers) and avoid the problems of precipitation and degradation in subsequent processing; in addition, maleic anhydride and alkyl acrylate monomers are added during the polymerization of the graft shell A2, and the acetylene alcohol surfactant is used in conjunction with the unreacted monomers to be grafted into the graft copolymer during the polymerization process, thereby reducing the residual aromatic vinyl monomers and acrylonitrile monomers; thus, the ABS resin prepared by mixing and extruding the obtained graft copolymer with the styrene-acrylonitrile copolymer has good processing performance, high gloss and surface energy, and at the same time gives the ABS resin low emission performance.
[0029] Further, the at least one grafting base A1 is obtained by the following emulsion polymerization:
[0030] A11: based on the graft base A1, 70 to 99.7 wt% of butadiene monomer; preferably 75 to 94 wt%, more preferably 78.5 to 85 wt%;
[0031] A12: based on the graft base A1, 0 to 29.7 wt% of at least one aromatic vinyl monomer; preferably 5 to 24 wt%, more preferably 13.5 to 20 wt%;
[0032] A13: 0.1 to 0.8 wt% of maleic anhydride based on the graft base A1; preferably 0.2 to 0.6 wt%, more preferably 0.3 to 0.5 wt%;
[0033] A14: based on the graft base A1, 0.1 to 0.8 wt% of an alkyl acrylate monomer; preferably 0.2 to 0.6 wt%, more preferably 0.3 to 0.5 wt%;
[0034] A15: based on the graft base A1, 0.1 to 0.8 wt% of an acetylenic alcohol surfactant; preferably 0.2 to 0.6 wt%, more preferably 0.3 to 0.5 wt%;
[0035] The sum of the weight percentages of A11, A12, A13, A14 and A15 is 100%.
[0036] Furthermore, the at least one graft shell A2 is obtained by emulsion polymerization of the following components in the presence of at least one graft base A1:
[0037] A21: 50 to 80 wt% of at least one vinyl aromatic monomer, based on the graft shell A2; preferably 55 to 75 wt%, more preferably 64.5 to 72 wt%;
[0038] A22: 15 to 45 wt% of acrylonitrile monomer based on graft shell A2; preferably 18.8 to 40 wt%, more preferably 22.5 to 30 wt%;
[0039] A23: 1 to 3 wt% maleic anhydride, based on graft shell A2; preferably 1.5 to 2.8 wt%, more preferably 2 to 2.5 wt%;
[0040] A24: 1 to 3 wt% of an alkyl acrylate monomer based on the graft shell A2; preferably 1.5 to 2.8 wt%, more preferably 2 to 2.5 wt%;
[0041] A25: Based on the graft shell A2, 0.1 to 0.8 wt% of an acetylenic alcohol surfactant; preferably 0.2 to 0.6 wt%, more preferably 0.3 to 0.5 wt%.
[0042] Furthermore, the aromatic vinyl monomer is one or more of styrene, α-methylstyrene or p-methylstyrene.
[0043] Furthermore, the acrylonitrile monomer is one or more of acrylonitrile, methacrylonitrile or acrylamide.
[0044] Furthermore, the structural formula of the acetylenic alcohol surfactant is shown in formula (I):
[0045]
[0046] Wherein, R1 is selected from H or R2 and R3 are selected from H or alkyl substituents, and R2 and R3 are not H at the same time; the number of carbon atoms of the alkyl substituent is less than 12; further, the number of carbon atoms of the alkyl substituent is less than 8;
[0047] When R1 is When R 12 and R 13 is selected from H or an alkyl substituent, and R 12 and R 13 are not H at the same time; the number of carbon atoms of the alkyl substituent is less than 12; further, the number of carbon atoms of the alkyl substituent is less than 8.
[0048] In a specific embodiment, the alkynol surfactant is one or more of methyl pentynol, 2,4,7,9-tetramethyl-5-decyne-4,7-diol, ethyl octynol or 2,5,8,11-tetramethyl-6-dodecyne-5,8-diol.
[0049] Specifically, the A15 and A25 may be the same or different. Preferably, the A15 and A25 are the same.
[0050] Optionally, one or more optional other components C1 are added. For example, the at least one other component C1 may be selected from one or more of a catalyst, an emulsifier, an initiator, a chain transfer agent or an electrolyte.
[0051] In the present invention, commonly used catalysts can be selected according to the prior art, such as but not limited to tetramethylethylenediamine and / or sodium formaldehyde hyposulfite.
[0052] In the present invention, commonly used emulsifiers can be selected according to the prior art, such as but not limited to one or more of potassium disproportionate rosin acid, potassium fatty acid, sodium dodecyl sulfonate or sodium dodecylbenzene sulfonate. In the present invention, the acetylene alcohol surfactant can play the role of an emulsifier, and a small amount of emulsifier can be added to the graft copolymer to avoid the problem caused by the emulsifier residue in the subsequent processing.
[0053] In the present invention, commonly used initiators can be selected according to the prior art, such as but not limited to one or more of potassium persulfate, ammonium persulfate or sodium persulfate.
[0054] In the present invention, a commonly used chain transfer agent can be selected according to the prior art, such as but not limited to n-dodecyl mercaptan and / or tert-dodecyl mercaptan.
[0055] In the present invention, commonly used electrolytes can be selected according to the prior art, such as but not limited to one or more of sodium carbonate, sodium bicarbonate, sodium hydroxide, potassium carbonate or potassium hydroxide.
[0056] The present invention also provides a method for preparing the graft copolymer composition, comprising the following steps:
[0057] S1. Before preparing at least one grafting base A1, part A15 is added, and then A11, A12, A13 and A14 are emulsion polymerized in the presence of part C1, and the remaining A15 is added at the end of the reaction and stirred to obtain a grafting base A1;
[0058] S2. In the presence of at least one grafting base A1 described in step S1 and the remaining part C1, A21, A22, A23 and A24 are emulsion polymerized, A25 is added during the emulsion polymerization, and then the graft copolymer composition is obtained by high temperature condensation.
[0059] Specifically, the emulsion polymerization in step S1 is a staged temperature increase polymerization.
[0060] More specifically, the staged temperature polymerization is specifically to heat the system to 50-60°C and react at a constant temperature for 6-10 hours as the first stage polymerization reaction, and the stirring speed is controlled at 90-120rpm; after the first stage polymerization reaction is completed, the system is heated to 65-72°C and reacted at a constant temperature for 10-15 hours as the second stage polymerization reaction, and the stirring speed is 110-130rpm; after the second stage polymerization reaction is completed, the temperature is raised to 75-85°C and the constant temperature reaction is carried out for 10-14 hours as the third stage reaction, and the stirring speed is controlled to 120-180rpm.
[0061] In a preferred embodiment, the graft copolymer is obtained in the form of a powder, i.e., the graft copolymer of step S2 is dried without adding other polymer components. The residual moisture of the obtained graft copolymer powder is less than or equal to 20wt%, preferably less than or equal to 10wt%, more preferably less than or equal to 8wt%.
[0062] Specifically, the residual moisture refers to the weight percentage of water contained in the graft copolymer composition obtained in step S2 without dehydration. Specifically, the residual moisture is determined by means of a suitable analytical device (e.g., a drying and weighing device), and the sample is dried until a constant sample weight is reached within a specified time. For example, the residual moisture of the graft copolymer can be measured at 180° C. in a halogen moisture analyzer HR73 from MettlerToledo until a constant weight is reached within 30 seconds.
[0063] In a specific embodiment, the preparation method comprises the following steps:
[0064] S1. Add water, initiator, electrolyte, chain transfer agent, emulsifier and part of A15 (e.g., 1% to 30% of the amount of A15) to a reactor (tank reactor), and stir at room temperature until completely dissolved and mixed; introduce nitrogen into the reactor to replace the air so that the oxygen content is less than 10 ppm, and then add A11, A12, A13 and A14 in proportion;
[0065] The reactor is heated to 50-60°C and reacted at a constant temperature for 6-10 hours for the first stage polymerization reaction, and the stirring speed is controlled at 90-120 rpm; after the first stage polymerization reaction, the system is heated to 65-72°C and reacted at a constant temperature for 10-15 hours for the second stage polymerization reaction, and the stirring speed is 110-130 rpm; after the second stage polymerization reaction, the system is heated to 75-85°C and reacted at a constant temperature for 10-14 hours for the third stage reaction, and the stirring speed is controlled to 120-180 rpm. At the end of the polymerization reaction, the remaining A15 (for example, 70% to 99% of the amount of A15) is added, and after stirring for half an hour, the temperature is lowered and the material is discharged to obtain the graft base A1;
[0066] S2. Heat the graft base A1 in step S1 to 50-60°C, add initiator, chain transfer agent, emulsifier, catalyst, and A21, A22, A23 and A24 and water, and continue to drop for 1.5-2.5 hours. After heating, continue to react for 2-4 hours, then add A25, and continue to react for 1.5-2.5 hours to obtain grafted latex; take the grafted latex and add it into a kettle reactor, heat it to 70-80°C, gradually add sulfuric acid thereto, add it over a period of 1.5-2.5 hours, and heat it to 90-99°C and maintain the temperature for 1.5-3 hours. Filter the obtained coagulated latex (for example, filter it with a 200-500 mesh filter), and dry it to obtain a graft copolymer composition with a moisture content of less than 1%.
[0067] The present invention also provides an ABS resin, wherein the ABS resin comprises:
[0068] D: 65 to 85 wt% of styrene-acrylonitrile copolymer;
[0069] A: 15 to 35 wt% of the above graft copolymer composition;
[0070] F: 0 to 20 wt% of at least one other polymeric component F, and
[0071] C2: 0 to 10 wt% of at least one other component C2.
[0072] Specifically, the styrene content in the styrene-acrylonitrile copolymer is 72 to 78 wt %.
[0073] In a specific embodiment, the other polymeric component F is selected from polycarbonate, polyamide and polyester.
[0074] In a specific embodiment, the other component C2 includes, but is not limited to, one or more of fillers, reinforcing agents, dyes, lubricants, release agents, stabilizers, antioxidants, UV absorbers, plasticizers, impact modifiers, antistatic agents, flame retardants, bactericides or foaming agents.
[0075] Specifically, the filler or reinforcing agent includes, but is not limited to, one or more of silicate, amorphous silicon dioxide, calcium silicate, quartz, mica, metal oxide, metal hydroxide, graphite, barium sulfate, calcium carbonate, magnesium carbonate, talc, kaolin, carbon fiber or glass fiber.
[0076] Specifically, the pigment includes but is not limited to one or more of titanium dioxide, phthalocyanine, ultramarine, iron oxide or carbon black.
[0077] Specifically, the stabilizer includes but is not limited to one or more of benzophenone, salicylate, benzotriazole or benzophenone.
[0078] Specifically, the release agent includes, but is not limited to, fatty acids having 12 to 30 carbon atoms, salts thereof, and derivatives thereof, such as stearic acid, stearate, palmitic acid, palmitate, stearyl alcohol, amide wax, polyolefin wax, and the like.
[0079] In the present invention, commonly used antioxidants can be selected according to the prior art, such as but not limited to one or more of hindered phenol antioxidants, phosphite antioxidants or thioester antioxidants.
[0080] Specifically, the hindered phenol antioxidant is one or more of N,N'-hexamethylenebis(3,5-di-tert-butyl-4-hydroxyphenylpropionamide, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], triethylene glycol bis-3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionate, β-(4-hydroxy-3,5-di-tert-butylphenyl)propionate n-octadecyl or spiroethylene glycol bis[β-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionate].
[0081] Specifically, the phosphite antioxidant is 2,4-di-tert-butylphenol and / or bis(2,6-di-tert-butyl-4-tolyl)pentaerythritol phosphite.
[0082] Specifically, the thioester antioxidant is one or more of distearyl thiodipropionate, dilauryl thiodipropionate or pentaerythritol dodecapropylthioate.
[0083] In the present invention, commonly used lubricants can be selected according to the prior art, such as but not limited to at least one of amide lubricants, stearate lubricants, ester lubricants or silicone lubricants.
[0084] The present invention also provides a method for preparing the ABS resin, comprising the following steps:
[0085] The graft copolymer composition, other polymer components F of the styrene-acrylonitrile copolymer and other components C2 are uniformly mixed and granulated by extrusion to obtain ABS resin.
[0086] Furthermore, the extrusion granulation adopts a twin-screw extruder.
[0087] Furthermore, the extrusion temperature is 200-300°C.
[0088] Furthermore, the screw speed of the twin-screw extruder is 200-300 rpm / min.
[0089] Furthermore, the screw length-to-diameter ratio of the twin-screw extruder is 18:1.
[0090] The present invention also provides application of the ABS resin in preparing automotive interior materials, kitchen appliances and electric tool materials.
[0091] Compared with the prior art, the present invention has the following beneficial effects:
[0092] The invention provides a graft copolymer composition. Maleic anhydride and alkyl acrylate monomers are introduced to improve the reaction conversion rate of monomers and reduce the residual butadiene content. Alkynol surfactants are used to be connected to the graft copolymer while playing an emulsifying role. ABS resin prepared by using the graft copolymer and styrene-acrylonitrile copolymer has excellent processing stability, high gloss, high surface energy and low emission. The above problems are solved from the perspective of production technology, and the types of ABS resin are increased. DETAILED DESCRIPTION
[0093] The present invention is further described in detail below in conjunction with specific examples, which are only used to explain the present invention and are not used to limit the scope of the present invention. The test methods used in the following examples are conventional methods unless otherwise specified; the materials and reagents used are reagents and materials that can be obtained from commercial channels unless otherwise specified.
[0094] The raw materials used in each embodiment and comparative example are:
[0095] A11: Butadiene monomer, industrial grade butadiene, purity greater than 96%, Huarui Chemical;
[0096] A12: aromatic vinyl monomer, styrene, purity greater than or equal to 99%, purchased from Aladdin Reagent Company;
[0097] A13: maleic anhydride, purity greater than or equal to 99%, purchased from Aladdin Reagent Company;
[0098] A14: alkyl acrylate monomer: methyl methacrylate, purity greater than or equal to 99%, purchased from Aladdin Reagent Company;
[0099] A15: Alkyne alcohol surfactant
[0100] A15-1: methylpentynol, purity greater than or equal to 99%, purchased from Aladdin Reagent Company;
[0101] A15-2: 2,4,7,9-tetramethyl-5-decyne-4,7,-diol, purity greater than or equal to 99%, purchased from Aladdin Reagent Company;
[0102] A15-3: 2,5,8,11-tetramethyl-6-dodecene-5,8-diol, purity greater than or equal to 99%, purchased from Aladdin Reagent Company;
[0103] A15-4: ethyl octynol, purity greater than or equal to 99%, purchased from Aladdin Reagent Company;
[0104] Other surfactants: organosiloxane surfactant, TEGOPREN 5840, purchased from Evonik;
[0105] A21: aromatic vinyl monomer, styrene;
[0106] A22: acrylonitrile monomer, acrylonitrile, purity greater than or equal to 99%, purchased from Aladdin Reagent Company;
[0107] A23: maleic anhydride, purity greater than or equal to 99%, purchased from Aladdin Reagent Company;
[0108] A24: alkyl acrylate monomer: methyl methacrylate, purity greater than or equal to 99%, purchased from Aladdin Reagent Company;
[0109] A25: Alkyne alcohol surfactant
[0110] A25-1: methylpentynol, purity greater than or equal to 99%, purchased from Aladdin Reagent Company;
[0111] A25-2: 2,4,7,9-tetramethyl-5-decyne-4,7,-diol, purity greater than or equal to 99%, purchased from Aladdin Reagent Company;
[0112] A25-3: 2,5,8,11-tetramethyl-6-dodecene-5,8-diol, purity greater than or equal to 99%, purchased from Aladdin Reagent Company;
[0113] A25-4: ethyl octynol, purity greater than or equal to 99%, purchased from Aladdin Reagent Company;
[0114] Other surfactants: organosiloxane surfactant, TEGOPREN 5840, purchased from Evonik;
[0115] Catalyst: tetramethylethylenediamine, purity greater than or equal to 99%, purchased from Aladdin Reagent Company;
[0116] Initiator: sodium persulfate, commercially available;
[0117] Electrolyte: sodium carbonate, commercially available;
[0118] Emulsifier: potassium disproportionate rosin acid, commercially available;
[0119] Chain transfer agent: tert-dodecyl mercaptan, commercially available;
[0120] Styrene-acrylonitrile copolymer: PN-118, styrene content of 75%, purchased from Chi Mei, Taiwan, China;
[0121] Other components C2:
[0122] Antioxidant: pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate (hindered phenol antioxidant) and tris(2,4-di-tert-butylphenyl) phosphite (phosphite antioxidant) are compounded in a weight ratio of 1:1 and are commercially available;
[0123] Lubricant: ethylene bisstearic acid amide, commercially available; it should be noted that the raw materials used in the parallel experiments of the embodiment and the comparative example are the same commercially available products.
[0124] Examples 1 to 8 and Comparative Examples 1 to 6
[0125] In the examples and comparative examples, the graft copolymer composition is prepared according to the formulations in Tables 1 to 2 by the following method, comprising the following steps:
[0126] S1. Based on the graft copolymer A, 100 wt% of water, 0.4 wt% of initiator, 0.6 wt% of chain transfer agent, 0.4 wt% of electrolyte, 0.4 wt% of emulsifier and part of A15 (20% of the amount of A15) were added to a reactor and stirred at room temperature until completely dissolved and mixed; nitrogen was introduced into the reactor to replace the air so that the oxygen content was less than 10 ppm, and then A11, A12, A13 and A14 were added in proportion;
[0127] The reactor was heated to 55°C and kept at this temperature for 9 hours as the first stage polymerization reaction, and the stirring speed was controlled to be 105 rpm; after the first stage polymerization reaction, the system was heated to 70°C and kept at this temperature for 12 hours as the second stage polymerization reaction, and the stirring speed was controlled to be 120 rpm; after the second stage polymerization reaction was completed, the system was heated to 75°C and kept at this temperature for 12 hours as the third stage reaction, and the stirring speed was controlled to be 130 rpm. At the end of the polymerization reaction, the remaining A15 (80% of the amount of A15) was added, stirred for half an hour, and then cooled and discharged to obtain the grafted base A1;
[0128] S2. The graft base A1 in step S1 is heated to 55°C, and based on the graft copolymer A, 0.4wt% initiator, 0.6wt% chain transfer agent, 0.4wt% emulsifier, 1wt% tetramethylethylenediamine, A21, A22, A23 and A24 and 120wt% water are added, and the addition is continued dropwise for 2h. After the heating is completed, the reaction is continued for 3h, and then A25 is added, and the reaction is continued for 2h to obtain a grafted latex; the grafted latex is added to a condensation reactor, heated to 75°C, sulfuric acid is gradually added thereto, and the addition is completed within 2h, and the temperature is raised to 95°C and maintained at the temperature for 2h. The obtained condensation latex is filtered through a 325-mesh filter and dried at 60°C for 2h in a fluidized bed dryer to obtain a grafted copolymer composition with a moisture content of less than 1%.
[0129] Table 1 Amount of each component in the graft copolymer composition in Examples 1 to 8 (unit: weight percentage)
[0130]
[0131] Note: The weight percentages of A1 and A2 are all based on graft copolymer A, and graft copolymer A accounts for more than 95wt% of the graft copolymer composition.
[0132] Table 2 Amount of each component in the graft copolymer composition in Comparative Examples 1 to 6 (unit: weight percentage)
[0133]
[0134] Note: The weight percentages of A1 and A2 are all based on graft copolymer A, and graft copolymer A accounts for more than 95wt% of the graft copolymer composition.
[0135] Specifically, the amounts of the components in A1 and A2 are shown in Tables 3-4.
[0136] Amount of each component in Table 3A1 (unit: percentage)
[0137]
[0138] Note: The weight percentages of A11, A12, A13, A14 and A15 are based on A1.
[0139] Table 4A2 Amount of each component (unit: percentage)
[0140]
[0141] Note: The weight percentages of A21, A22, A23, A24 and A25 are based on A2.
[0142] Examples 9 to 18 and Comparative Examples 7 to 12
[0143] In Examples 9 to 18 and Comparative Examples 7 to 12, the ABS resin is prepared according to the formulations in Tables 5 to 6 by the following method, comprising the following steps:
[0144] The graft copolymer composition, styrene-acrylonitrile copolymer and other component C2 are mixed uniformly, and granulated by extrusion through a twin-screw extruder to obtain ABS resin; the extrusion temperature is 200-300°C, the screw speed is 250rpm, and the screw aspect ratio is 18:1.
[0145] Table 5 ABS resin formulations in Examples 9 to 18 (unit: weight percentage)
[0146]
[0147]
[0148] Table 5 ABS resin formulations in Comparative Examples 7 to 12 (unit: weight percentage)
[0149]
[0150]
[0151] Performance Testing
[0152] The ABS resin prepared in the above examples and comparative examples was subjected to performance tests, and the specific test items and test methods are as follows:
[0153] 1. Test method:
[0154] (1) Processing stability test: A KraussMaffei injection molding machine was used to select a water splash verification sample mold. The above-mentioned ABS resin was used to injection mold a 45 mm*65 mm*2 mm sample. The injection molding temperature was 250°C. After a 10-min heat retention, another sample was injection molded. The appearance of the sample was statistically analyzed, and the area of the sample material flower was calculated and presented as a percentage.
[0155] (2) Surface energy test: A KraussMaffei injection molding machine was used to select a high-gloss color plate mold for injection molding at 220°C and medium-high pressure conditions to obtain a 45mm*65mm*2mm high-gloss color plate and test it; specifically, a wettability measurement (surface energy) kit (ACCY DYNE TESTTM) was used. This kit contains 6 different DYNE pens with a surface energy measurement range of 38 dynes / cm to 48 dynes / cm. When the surface energy of the high-gloss color plate matches the surface energy of the ink, the ink is observed to diffuse evenly without boundary contraction and is recorded accordingly. The higher the dyne value, the better the surface performance of the material.
[0156] (3) Glossiness test: The ABS resins prepared in the above-mentioned embodiments and comparative examples were tested according to the test standard of "Plastic Specular Gloss Test Method", the standard number is GB / T 8807-1988, and the incident angle is 60°;
[0157] (4) Odor test: The ABS resins prepared in the above examples and comparative examples were tested according to Ford automobile test standard BO131-03 2012; the evaluation criteria are as follows:
[0158]
[0159]
[0160] (5) Test of the content of volatile substances (styrene): The ABS resins prepared in the above-mentioned embodiments and comparative examples were tested according to the standard GB / T16867-1997. The specific test method is as follows: in a headspace bottle, the sample is dissolved or swelled in N,N-dimethylformamide, n-butylbenzene is used as the internal standard, the headspace bottle is sealed, and it is placed at a certain temperature for a certain period of time for thermal equilibrium, a certain amount of thermal equilibrium is drawn and neatly injected into the chromatograph for GC quantitative analysis, and the amount of residual styrene is calculated based on the peak areas of styrene and n-butylbenzene; headspace conditions: 120°C, 30 min; GC conditions: chromatographic column: DB-5ms, 50m×0.32um×0.32um; injection volume: 2ml; injection port temperature: 200°C; split ratio: 50:1; gas flow rate: 2ml / min; heating program: 50°C (holding for 3min)→10°C / min, 200°C (holding for 5min); carrier gas: He.
[0161] 2. Test results
[0162] The test results are shown in Table 6.
[0163] Table 6 Test results of embodiments and comparative examples
[0164]
[0165]
[0166] It can be seen from Table 6 that the ABS resin prepared by mixing and extruding the graft copolymer prepared by the present invention and the styrene-acrylonitrile copolymer has good processing performance, high surface energy and gloss, and low content of volatile substances; specifically: the surface flower of the ABS resin does not exceed 10%, the surface energy is not less than 44, the gloss is not less than 94, the odor level does not exceed 4.0, and the styrene content is not higher than 800ppm.
[0167] It can be seen from Examples 9 to 12 that when the acetylene alcohol surfactant is one or more of methylpentynol, 2,4,7,9-tetramethyl-5-decyne-4,7-diol or 2,5,8,11-tetramethyl-6-dodecyne-5,8-diol, the comprehensive performance of the obtained ABS resin is better.
[0168] It can be seen from Comparative Examples 7 and 8 that when no alkyl acrylate monomer or maleic anhydride is added to the graft shell A2, the comprehensive properties of the ABS resin obtained after co-extrusion with the styrene-acrylonitrile copolymer are significantly reduced, especially the surface flower is significantly increased, and there is a strong pungent odor, and the styrene content is not less than 1200ppm.
[0169] It can be seen from Comparative Example 9 that if no acetylenic alcohol surfactant is added, the comprehensive performance of the ABS resin obtained after co-extrusion with styrene-acrylonitrile copolymer is significantly reduced, especially the surface flower is as high as 45%, the surface energy is only 38, and the styrene content is not less than 1424ppm.
[0170] It can be seen from Comparative Examples 10 and 11 that if no alkyl acrylate monomer or maleic anhydride is added in the preparation of the graft base A1, the surface of the prepared ABS resin has more material flowers and a more serious odor, which cannot meet the requirements.
[0171] It can be seen from Comparative Example 12 that if other surfactants are used instead of acetylene alcohol surfactants, the comprehensive performance of the ABS resin obtained after co-extrusion with styrene-acrylonitrile copolymer is significantly reduced, there are more material flowers on the surface, the odor is serious, the styrene content is high, and it cannot meet the requirements.
[0172] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A graft copolymer composition, characterized in that: The graft copolymer composition comprises: A: 95 to 99.9 wt% of at least one graft copolymer A comprising: Based on the graft copolymer A, 55 to 79.9 wt % of at least one graft base A1 obtained by emulsion polymerization of the following components: A11: 60 to 99.7 wt % of butadiene monomer, based on the graft base A1; A12: 0 to 39.7 wt % of at least one aromatic vinyl monomer, based on the graft base A1; A13: 0.1 to 1 wt % of maleic anhydride based on the graft base A1; A14: based on the grafting group A1, 0.1 to 1 wt % of an alkyl acrylate monomer, wherein the alkyl acrylate monomer is at least one of a C1-C8 alkyl methacrylate or a C1-C8 alkyl acrylate; A15: 0.1 to 1 wt% of an acetylenic alcohol surfactant based on the graft base A1; wherein the sum of the weight percentages of A11, A12, A13, A14 and A15 is 100%; and 28 to 49.9 wt %, based on the graft copolymer A, of at least one graft shell A2, obtained by emulsion polymerization in the presence of at least one graft base A1: A21: 40 to 99.7 wt % of at least one vinyl aromatic monomer, based on graft shell A2; A22: 0 to 50 wt % of acrylonitrile monomer based on graft shell A2; A23: 0.1 to 5 wt % maleic anhydride, based on graft shell A2; A24: based on the graft shell A2, 0.1 to 5 wt% of an alkyl acrylate monomer, wherein the alkyl acrylate monomer is at least one of a C1-C8 alkyl methacrylate or a C1-C8 alkyl acrylate; A25: 0.1 to 1 wt% of an acetylenic alcohol surfactant based on the graft shell A2; Wherein, the sum of the weight percentages of A21, A22, A23, A24 and A25 is 100%; The sum of the weight percentages of A1 and A2 is 100%, and C1: 0.1 to 5 wt% of at least one other component C1; The structural formula of the acetylenic alcohol surfactant is shown in formula (I): (Ⅰ); Wherein, R1 is selected from H or ; R2 and R3 are selected from H or alkyl substituents, and R2 and R3 are not H at the same time; R 12 and R 13 is selected from H or an alkyl substituent, and R 12 and R 13 The alkyl substituent has less than 12 carbon atoms.
2. The graft copolymer composition according to claim 1, characterized in that: The alkyl substituent has less than 8 carbon atoms.
3. The graft copolymer composition according to claim 1, characterized in that: The alkynol surfactant is one or more of methyl pentynol, 2,4,7,9-tetramethyl-5-decyne-4,7-diol, ethyl octynol or 2,5,8,11-tetramethyl-6-dodecyne-5,8-diol.
4. The graft copolymer composition according to claim 1, characterized in that: The aromatic vinyl monomer is one or more of styrene, α-methylstyrene or p-methylstyrene.
5. The graft copolymer composition according to claim 1, characterized in that: The acrylonitrile monomer is acrylonitrile and / or methacrylonitrile.
6. The graft copolymer composition according to claim 1, characterized in that: The other components C1 include one or more of a catalyst, an emulsifier, an initiator, a chain transfer agent or an electrolyte.
7. A method for preparing the graft copolymer composition according to any one of claims 1 to 6, characterized in that: The steps include: S1. Before preparing at least one graft base A1, part A15 is added, and then A11, A12, A13 and A14 are emulsion polymerized in the presence of part C1, and the remaining A15 is added at the end of the reaction and stirred to obtain a graft base A1; S2. In the presence of at least one grafting base A1 described in step S1 and the remaining part C1, A21, A22, A23 and A24 are emulsion polymerized, A25 is added during the emulsion polymerization, and then the graft copolymer composition is obtained by high temperature condensation.
8. The preparation method according to claim 7, characterized in that: The emulsion polymerization in step S1 is a staged temperature-raising polymerization.
9. The preparation method according to claim 8, characterized in that: The staged temperature-raising polymerization is specifically as follows: heating the temperature to 50-60° C. and reacting at the constant temperature for 6-10 hours as the first stage polymerization reaction, and controlling the stirring speed at 90-120 rpm; after the first stage polymerization reaction is completed, heating the system to 65-72° C. and reacting at the constant temperature for 10-15 hours as the second stage polymerization reaction, and stirring the system at the stirring speed of 110-130 rpm; after the second stage polymerization reaction is completed, heating the system to 75-85° C. and reacting at the constant temperature for 10-14 hours as the third stage reaction, and controlling the stirring speed to 120-180 rpm.
10. An ABS resin, characterized in that: The ABS resin comprises: D: 65 to 85 wt% of a styrene-acrylonitrile copolymer; A: 15 to 35 wt% of the graft copolymer composition according to any one of claims 1 to 6; F: 0 to 20 wt% of at least one other polymeric component F, and C2: 0 to 10 wt % of at least one other component C2.
11. The ABS resin according to claim 10, characterized in that: The further polymeric component F is selected from the group consisting of polycarbonates, polyamides and polyesters.
12. A method for preparing ABS resin, characterized in that: The steps include: The styrene-acrylonitrile copolymer, the graft copolymer composition according to any one of claims 1 to 6, other polymer components F and other components C2 are uniformly mixed, and ABS resin is obtained by extrusion granulation.
13. Use of the ABS resin according to claim 10 or 11 in the preparation of automotive interior / exterior materials, kitchen appliances, OA office and power tool materials.
Citation Information
Patent Citations
Low individual color thermoplastic molding material
CN1269808A
Coating composition for interior material of car and interior material for car
JP2006176729A
Water-repellent composition
US20210363280A1
Cited By
PC / ABS alloy with high surface tension
CN121450079A